Studi Perbandingan Aktivitas Harian Kelompok Lutung jawa Betina (Trachypithecus auratus) Sebelum dan Sesudah Dilepasliarkan Di Hutan Lindung Coban Talun - Putri, Febrian Priska Amalia; Santoso, Hari; Zayadi, Hasan (Jurnal SAINS ALAMI (Known Nature), 2022)
The population of east javan langur (Trachypithecus auratus) the number in nature continues to decrease, rehabilitation is one way to preserve the population. This study aims to compare the daily activity before and after release the east javan langur. To approach the aim of the study, the researcher used focal animal sampling and scans sampling and noted with Instantaneous Sampling then calculated the percentage.  Data of the observation obtained by recording the daily activities of east javan langur in the barn or in the nature  includes the movement activity (walking, running, jumping and climbing) break time activity (sit back, sit alert, standing, sleeping, prone and supine),  agononistic social activity ( sound, chase, and snatch the food, hit and fight),  grooming activity (allo-grooming and auto-grooming) eat, drink, urination and defecation. The finding of this research showed that the presentation of daily activities of east javan langur in the barn is first, the break time activity (42, 9%), second, eat and drink activity (24, 1%), grooming (18.6%), movement (8.2%), social agonistic (3.3%), urination and defecation (2.3%) and  sexual (0.6%).  Then for the daily activities in the nature, movement (34.6%), break time activity (29.0%), eat and drink (22.7%), grooming (8.7%), urination and defecation (0.9%) and sexual (0%). The tentative conclusion before the high released activity in the nature is the break time activity. the highest activity of east javan langur presumed freedom of location area to doing activity like movement, temperature intensity, feed abundance and the presence of the opposite sex.Keywords: Javan Langur, Comparison of Activity, FactorABSTRAKPopulasi Lutung Jawa (Trachypithecus auratus) jumlahnya di alam terus menurun, salah satu usaha pelestarianya dengan melakukan rehabilitasi. Tujuan penelitian untuk mengetahui perbandingan aktivitas harian sebelum dan sesudah pelepasliaran Lutung Jawa. Metode yang digunakan yaitu Focal Animal Sampling dan Scan Sampling dengan pencatatan Instantaneous Sampling kemudian dihitung persentasenya. Data pengamatan diperoleh dari pencatatan aktivitas harian lutung jawa di kandang maupun di hutan meliputi aktivitas bergerak (berjalan, berlari, melompat dan memanjat), aktivitas istirahat (duduk rileks, duduk waspada, berdiri, tidur, menelungkup dan terlentang), aktivitas sosial-agonistik (bersuara, mengejar, merebut makanan, memukul dan berkelahi), aktivitas grooming (allo-grooming dan auto-grooming), makan, minum, urinasi dan defekasi. Hasil penelitian menunjukkan persentase aktivitas di kandang yakni istirahat (42.9%), makan dan minum (24.1%), grooming (18.6%), bergerak (8.2%), sosial agonistic (3.3%), urinasi dan defekasi (2.3%) dan seksual (0.6%). Untuk aktivitas harian di hutan yakni bergerak (34.6%), istirahat (29.0%), makan & minum (22.7%), grooming (8.7%), urinasi dan defekasi (0.9%) dan seksual (0%). Kesimpulan sementara sebelum dilepasliarkan aktivitas tertinggi dalam kandang adalah istirahat. Setelah dilepasliarkan aktivitas tertinggi di hutan bergerak bebas. Tingginya aktivitas lutung jawa diduga kebebasan luasan lokasi untuk bergerak, intensitas suhu, kelimpahan pakan dan adanya lawan jenis.Kata kunci : Lutung Jawa, Perbandingan Aktivitas, Faktor